Computerized Accounting Integration into High School Curriculum Delivery: Benefits and Barriers - Mdingi, Mvemve (The Indonesian Journal of Accounting Research, 2024)
Education without integrating computer applications in this 21st century deprives learners of the experience and exposure of linking education to real-world job processes. In South Africa, higher education institutions have long integrated computerized accounting systems into their accounting qualifications curriculum. However, that is not the case with the high school accounting curriculum. This paper aims to investigate the benefits and barriers of integrating computerized accounting into the high school accounting curriculum. This is a case study design. Data was collected from purposively selected high school accounting teachers using semi-structured interviews. The interview transcripts were entered into the Atlas.ti software. The discourse analysis method was used to interpret and evaluate the meaning of emerging themes. The findings indicate that integrating computerized accounting into curriculum delivery would develop interest and positive attitudes among learners towards accounting, enhance their understanding of accounting principles, improve their academic performance, and attract them into the accounting profession. Unavailability of resources and lack of funding were identified as barriers that can impede the integration of computerized accounting into high school curriculum delivery.